Control of Liquid Sloshing Container Using Active Force Control Method - Didik Setyo Purnomo; Adnan Rachmad Anom Besari; Zaqiatud Darojah (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
This  paper  presents  a  robust  control  method  to  relieve  the  sloshing  of  liquid container transport using Active Force Control (AFC) method. A model of two degree-of- freedom (2-DOF)  liquid  container  transfer  was implemented  in this research as  the  main dynamical system to be controlled. The surface of liquid is maintained in a flat position, so that changes the slope of liquid surface countered by changing the acceleration of container. The focus of this research is how to use AFC method being applied to the system, so that it can suppress liquid sloshing. The control scheme were simulated, compare between PID-AFC and pure PID.  Simulations has been conducted, the results show that the PID-AFC have superior performance to suppress the sloshing compared with pure PID, especially if disturbance occurred.